PELATIHAN PENYUSUNAN MANDARIN FOR STORY TELLING UNTUK PENGEMBANGAN POTENSI DESA WISATA CIKAKAK SEBAGAI OBYEK RURAL TOURISM - Hariyadi, Bagus Reza; Firmansyah, Dian Bayu; Prasetyowati, Henggar; Oktavilia, Ernasiwi Astri; Herliana, Monika (Nindikayla Institute, 2023)
Cikakak Tourism Village is one of the Advanced Stage Tourism Villages in Wangon District, Banyumas Regency, which is a form of achievement in the realm of tourism. The combination of natural, cultural, and religious potentials in Cikakak village has the potential to be developed as a rural tourism area. To entertain and accompany tourists visiting Cikakak village, a Tour Guide is able to tell the details of tourist attractions and ensure tourists obtain educational value. Based on the results of observations in the field, it is known that the Saka Tunggal Tourism Awareness Group has not been able to be creative in assembling and creating information on village potential that is told narratively (storytelling) to be able to attract foreign tourists, especially Chinese tourists. From the results of the Mandarin for storytelling training, it can be concluded that from the aspect of knowledge, the trainees have a good understanding of how to use storytelling as a promotional medium for Cikakak's Tourism Village. However, from the aspect of skills in producing website content and video storytelling, further assistance is still needed to be able to produce Mandarin for Storytelling content that is more interactive and raises the values and attractions possessed by Ciadik Village as a cultural tourism destination.